Esterification Prevents Induction of the Mitochondrial Permeability Transition by N-Acetyl Perfluorooctane Sulfonamides - O'Brien, Timothy M. (2006)
N-Alkyl perfluorooctane sulfonamides have been widely used as surfactants on fabrics and papers, fire retardants, and anticorrosion agents, among many other commercial applications. The broad use, global distribution, and environmental persistence of these compounds has generated considerable interest regarding potentially toxic effects. We have previously reported that perfluorooctanesulfonamidoacetate (FOSAA) and N-ethylperfluorooctanesulfonamidoacetate (N-EtFOSAA) induce the mitochondrial permeability transition (MPT) in vitro, resulting in cytochrome c release, inhibition of respiration, and generation of reactive oxygen species. By synthesizing the corresponding methyl esters of FOSAA and N-EtFOSAA (methyl perlfuorinated sulfonamide acetates), we tested the hypothesis that the N-acetate moiety of FOSAA and N-EtFOSAA is the functional group responsible for induction of the MPT. Swelling of freshly isolated liver mitochondria from Sprague−Dawley rats was monitored spectrophotometrically and membrane potential (ΔΨ) was measured using a tetraphenylphosphonium-selective (TPP+) electrode. In the presence of calcium, 40 μM FOSAA and 7 μM N-EtFOSAA each induced mitochondrial swelling and a biphasic depolarization of membrane potential. Mitochondrial swelling and the second-phase depolarization were inhibited by cyclosporin-A or the catalyst of K+/H+ exchange nigericin, whereas the first-phase depolarization was not affected by either. In contrast, the methyl esters of FOSAA and N-EtFOSAA exhibited no depolarizing or MPT inducing activity. Results of this investigation demonstrate that the carboxylic acid moiety of the N-acetates is the active functional group, which triggers the MPT by perfluorinated sulfonamides.